Corrigendum Candidate Gene Locus for PHACE Syndrome. Am J Med Genet A. 2012;158(6):1363–1367. Doi:10.1002/ajmg.a.35341 (American Journal of Medical Genetics Part A, 2022)
Peroxisomal fatty acyl-CoA reductase 1 (FAR1) deficiency is a rare single-enzyme peroxisomal disorder caused by biallelic pathogenic variants in FAR1, typically manifesting with severe neurodevelopmental delay, hypotonia, early-onset epilepsy, and congenital cataracts. We report a male infant born to first-cousin parents presenting with severe global developmental delay, refractory seizures, progressive microcephaly, and feeding difficulties, together with a previously unreported finding of imperforate anus. Ophthalmologic examination revealed abnormal macular reflexes without overt cataracts. Brain MRI at 14 months showed diffuse bilateral subcortical and periventricular T2/FLAIR hyperintensities consistent with chronic white matter disease. Metabolic screening was normal. Rhizomelic chondrodysplasia punctata was excluded, and whole-exome sequencing identified a homozygous likely pathogenic canonical splice-site variant (NM_032228.3:c.-7-2A>G) in FAR1. Functional cDNA analysis confirmed skipping of exon 2, supporting a loss-of-function mechanism. Segregation analysis confirmed autosomal recessive inheritance. This single-case observation raises the possibility that the phenotypic spectrum of FAR1 deficiency may extend to gastrointestinal malformations such as imperforate anus, highlights the limitations of routine biochemical testing, and underscores the importance of early whole-exome sequencing for definitive diagnosis and multidisciplinary management.